Structure Of Human Skeleton Exhibits The Mysterious Love Of Allah (Swt) To Prophet Muhammad (Saw) - Mohammad Abul Hossain (Ar-Raniry: International Journal of Islamic Studies, 2018)
This study presents a scientific explanation of a very important verse (Ayat), 95:4 in the holy Qur’an. The verse is in sura At-Tin, states that:  ﻟَﻘَﺪْ ﺧَﻠﻘْﻨَﺎ اﻹِﻧﺴَﺎنَ ﻓِﻲ ٲَﺣْﺴَنِ ﺗَﻘْﻮِﻳﻢِ : "Verily, We created man in the best statue (mould)”. In response to the “best statue”, a mysterious observation is proposed by  correlating the four oaths of Allah (Sobhan wa tawla: SWT) which imposed before starting this verse, with the help of physical structure of oath materials, knowledge of medical science and other verses in the holy Qur’an. That is – the statue of human body (Adam) represents the combine structure of Arabic words (ﻣﺤﻤﺪ) Muhammad (Peace be upon him: PBUH) and (اﻟﻠﻪ) Allah (SWT), which made his (Adam) superiority to all others. Thus humans became the topmost creature in the whole universe, and his body structure is created in the best statue, mentioned in the verse of the holy Qur’an. Actually, the creation of such a structure of the human body is the outlook of the infinite love of Allah (SWT) to His prophet Muhammad (SAW). Regarding this, supporting verses in the holy Qur’an are discussed.